2013
DOI: 10.1186/1471-2474-14-361
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course over the first year of Whiplash Associated Disorders (WAD): pain-related disability predicts outcome in a mildly affected sample

Abstract: BackgroundDifferent recovery patterns are reported for those befallen a whip-lash injury, but little is known about the variability within subgroups. The aims were (1) to compare a self-selected mildly affected sample (MILD) with a self-selected moderately to severely affected sample (MOD/SEV) with regard to background characteristics and pain-related disability, pain intensity, functional self-efficacy, fear of movement/(re)injury, pain catastrophising, post-traumatic stress symptoms in the acute stage (at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Our finding that lower disability levels are a predictor of success for cRFN is not surprising. The presence of higher disability levels (NDI > 28%) in the acute stage of WAD has frequently been shown to predict poor long‐term health outcomes following the injury, with our study demonstrating the complementary finding that lower disability is a predictor of responsiveness to cRFN. Our previous results also demonstrated that individuals who did not respond to initial facet joint block injections (prior to undergoing cRFN) presented with higher levels of pain catastrophizing .…”
Section: Discussionsupporting
confidence: 60%
“…Our finding that lower disability levels are a predictor of success for cRFN is not surprising. The presence of higher disability levels (NDI > 28%) in the acute stage of WAD has frequently been shown to predict poor long‐term health outcomes following the injury, with our study demonstrating the complementary finding that lower disability is a predictor of responsiveness to cRFN. Our previous results also demonstrated that individuals who did not respond to initial facet joint block injections (prior to undergoing cRFN) presented with higher levels of pain catastrophizing .…”
Section: Discussionsupporting
confidence: 60%
“…There is preliminary evidence showing that kinesiophobia34–37 and pain catastrophising34 37 38 may be associated with the course of neck symptoms following a whiplash injury facilitating the transition from acute to chronic WAD. However, findings of these preliminary studies remain inconsistent34–38 regarding both the strength and even the direction of the associations. Several systematic reviews14 39–42 have analysed whether pain catastrophising and kinesiophobia are prognostic factors of WAD chronicity.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that lower disability levels are a predictor of success for cervical RFN is not surprising. The presence of higher disability levels (NDI > 28%) in the acute stage of WAD has frequently been shown to predict poor long-term health outcomes following the injury [6,231,421,426,427], with our study demonstrating the complementary finding that lower disability is a predictor of responsiveness to cervical RFN. Our previous results also demonstrated that individuals who did not respond to initial facet joint block injections (prior to undergoing cervical RFN) presented with higher levels of pain catastrophizing [413].…”
Section: Discussionsupporting
confidence: 71%